(untitled) (REMUNOM, 2023)
This work had the objective of identifying and analyzing how the lack of accessibility of the Basic Health Units interferes in the care of the elderly, since, according to the Brazilian Institute of Geography and Statistics (IBGE), the population segment that increases the most in the population Brazilian is that of elderly people, with growth rates of more than 4% per year for the decade from 2012 to 2022, representing, in the same period, an average increase of more than 1 million elderly people per year. Accessibility is a constant concern for the elderly, and with the increase of this public in the country, the concern with access to health grows together, both with regard to the infrastructure of these Units, and in relation to the humanized reception. The term accessibility, which was discussed in this study, was related to the ease of using health services, thus promoting integrality, equity, universality and social participation. This study primarily consists of analyzing these difficulties, aiming at an improvement to be adopted, in which there is relevant prioritization to those who need shelter, especially the elderly, in order to be able to positively interfere in the health status of this public. For that, a qualitative methodology was used, based on studies related to the theme. As a research technique for data collection and analysis, a bibliographic review was used, with the intention of describing the object of study. In the end, the importance of accessibility was considered for the quality of care for the elderly in the UBS, inserting it in a comprehensive and individualized view, seeking to help them within their needs. It was evidenced how adequate assistance, trained professionals, adapted spaces bring more security and comfort in the care of the elderly, who with this can realize their importance in society and thus take care of their health in a more humane way.